Advance Arabic Grammar for Academic Purposes (Part Two-Verbal Sentence) - Dollah, Nafi@Hanafi (2002)
Abstract The book (Advanced Arabic Grammar for Scientific Purposes- Verbal Sentence) is a reference to a sophisticated style of literature that takes into consideration a set of fundamentals that enable the student to assimilate the grammatical system at its advanced level, and aims to enable students to assimilate this grammar system through a scientific study of the structure of Arabic syntax. In this composition we take into account different grounds, including: the attempt of the book to define the students with a true concept of the Arabic sentence. In this we have benefited from the findings of modern linguistic studies, as well as the heritage sources, and achieved a pairing between old and modern. In these margins we have pointed out these valuable sources for further information. We have included the Qur'anic texts that are directly related to the latest subjects in order to move scholars to the rules applicable to the texts and to provide practical training on the studied rules. The Objectives of the Disclosure were to take benefit from the findings of modern linguistic studies, as well as the heritage sources, and achieved a pairing between old and modern as well as to o include the Qur'anic texts that are directly related to the latest subjects in order to move scholars to the rules applicable to the texts and to provide practical training on the studied rules.